2008
DOI: 10.1002/mds.22219
|View full text |Cite
|
Sign up to set email alerts
|

Walking speed during single and dual tasks in Parkinson's disease: Which characteristics are important?

Abstract: The impact of dual tasks on gait in Parkinson's disease (PD) reveals lack of automaticity and increased cognitive demands. We explored which characteristics explained walking speed with and without dual task interference and if they reflected the cognitive demands of the task. In 130 people with PD, gait performance was quantified in the home using accelerometers allowing estimates of single and dual task walking speed and interference (difference between dual and single task). Multiple regression analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
95
2
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 28 publications
14
95
2
9
Order By: Relevance
“…Disparities in testing protocols and disease duration between the samples (mean 13 years), compared to the current study (mean 6 years) may account for these observed differences (Sustakoski, Perera, VanSwearingen, Studenski, & Brach, 2015). Although similar investigations of the relationships between the Walk‐12G and performance‐based gait measures are lacking, fear of falling has been associated with slower gait speeds in healthy older adults (Maki, 1997) and people with PD (Bryant, Rintala, Hou, & Protas, 2014; Rochester et al., 2008). Additionally, Curtze et al.…”
Section: Discussionmentioning
confidence: 99%
“…Disparities in testing protocols and disease duration between the samples (mean 13 years), compared to the current study (mean 6 years) may account for these observed differences (Sustakoski, Perera, VanSwearingen, Studenski, & Brach, 2015). Although similar investigations of the relationships between the Walk‐12G and performance‐based gait measures are lacking, fear of falling has been associated with slower gait speeds in healthy older adults (Maki, 1997) and people with PD (Bryant, Rintala, Hou, & Protas, 2014; Rochester et al., 2008). Additionally, Curtze et al.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic PD results from basal ganglia dysfunction, and as a consequence, task automaticity is reduced and cognitive resources must be drawn on to maintain performance of both tasks. Studies investigating the impact of concurrent tasks on gait in PD reveal lack of automaticity and increased cognitive demands (Rochester, Nieuwboer, Baker, Hetherington, Willems, Kwakkel, Wegen, Lim, & Jones, 2008).…”
Section: Concurrent Task Effects In Parkinson's Diseasementioning
confidence: 99%
“…Consequently, individuals with basal ganglia dysfunction will have difficulty coping with concurrent tasks, and performance deficits are often exacerbated in individuals with PD (Rochester et al, 2008). …”
Section: Concurrent Task Effects In Parkinson's Diseasementioning
confidence: 99%
See 2 more Smart Citations